(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
No matter how global the fight against psychotropics and drug addiction becomes, one has the impression that humanity’s susceptibility to this disaster is increasing. According to the data published in the journal, 14 million to 56 million people use amphetamines, 12 million to 21 million people use opium, and 14 million to 21 million people use cocaine. More than 20 million people in the world take drugs by injection. Counting these millions makes one dizzy. However, at the root of this is a problem that is taking people’s lives and is considered the lifeline of our lives, and you are worried.